Konseling Karir dengan Menggunakan Career Information-Processing Model untuk Membantu Career Decision-Making - Fatma Nur Aqmarina; Riana Sahrani; Rahmah Hastuti (Psympathic : Jurnal Ilmiah Psikologi, 2017)
Having graduated from senior high school, most of high school students continue their education to university level. This research aimed to find effectiveness of career counseling by using career information-processing model to assist career decision-making for students of MAN Y Jakarta. The career information-processing model emphasizes the mind and memory in the process of problem solving and career decision-making (Henderson, 2009). This research used quasi-experiment one group pre-test post-test design involving 7 participants who previously experienced the obstacle in career decision-making. The career counseling intervention was implemented in 9 sessions. Based on paired sample t-test (t=8.576, p<.01), result showed that career counseling intervention was effective to assist career counseling for students of MAN Y Jakarta. Thus, intervention in this study could serve as a model of intervention to assist students in career decision-making.